System Dynamics Modeling for Clean Water Management in the Sleman Regency - Widodo Brontowiyono; M. M. Lanny W. Pandjaitan; Lukas Lukas; Lukman Hidayat; Ribut Lupyanto; Kasam Kasam (School of Postgraduate Studies, Diponegoro Univer, 2025)
As the regional organization responsible for fulfilling the community's water demands, the Municipal Waterworks in Indonesia, Perusahaan Daerah Air Minum (PDAM), is expected to ensure consistent and equitable distribution of clean water. However, water leaks and other issues in PDAMs tend to reduce the amount of water distributed to the community. An initiative to address water demands at the provincial level has been implemented, placing specific emphasis on the distribution of bulk water across regencies and cities. This initiative is classified as a fundamental service under the Minimum Service Standards (MSS), which aim to improve the availability of water resources. STELLA 9.1.3 software is used in this study to run a policy model simulation and determine the best possible policy scenario for clean water management in Sleman Regency. Sleman Regency is expected to have a water deficit of 144 liters per second in 2035, according to water balance modeling conducted under Business as Usual (BaU) conditions. According to the policy scenario simulation results, show that reducing air leakage by up to 20% and implementing a strategy for maximizing air flow utilization (100%) between districts/cities can increase water availability by 283.72 liters per second.